2004
DOI: 10.1074/jbc.m314142200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Activation of c-Jun N-terminal Kinase in Vivo Induces Restrictive Cardiomyopathy and Conduction Defects

Abstract: The stress-activated protein kinase, c-Jun N-terminal kinase (JNK), has been implicated in the process of cardiac hypertrophy and apoptosis, yet the specific roles of JNK in heart failure are unclear. To determine the effects of JNK activation in intact heart, we established transgenic animals using a Cre/loxP-mediated gene switch approach to achieve targeted expression of an upstream activator, mitogen-activated protein kinase kinase 7 (D) (MKK7D), in ventricular myocytes. MKK7D expression led to significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 66 publications
8
84
1
3
Order By: Relevance
“…This increase in cardiac hypertrophy associated with p38 or JNK inhibition was reversed by deletion of calcineurin Aβ, showing that calcineurin-NFAT signaling was a mechanism whereby these kinases mediated their antihypertrophic effect. That JNK and p38 can have an antihypertrophic effect is also somewhat consistent with the phenotype of mice with MKK3/6 or MKK7 overexpression in the heart, which showed severe cardiac dilation and failure without prominent hypertrophy (39,40). We also previously showed that Jnk1 +/-Jnk2 -/-mice developed spontaneous cardiac hypertrophy with aging and that young mice subjected to TAC had a greater hypertrophic response (27).…”
Section: Discussionsupporting
confidence: 78%
“…This increase in cardiac hypertrophy associated with p38 or JNK inhibition was reversed by deletion of calcineurin Aβ, showing that calcineurin-NFAT signaling was a mechanism whereby these kinases mediated their antihypertrophic effect. That JNK and p38 can have an antihypertrophic effect is also somewhat consistent with the phenotype of mice with MKK3/6 or MKK7 overexpression in the heart, which showed severe cardiac dilation and failure without prominent hypertrophy (39,40). We also previously showed that Jnk1 +/-Jnk2 -/-mice developed spontaneous cardiac hypertrophy with aging and that young mice subjected to TAC had a greater hypertrophic response (27).…”
Section: Discussionsupporting
confidence: 78%
“…The effects of Lmna mutations on proteins particularly important for conduction system structure or function might weaken these specialized cells and promote early apoptotic death. Activation of c-jun N-terminal kinase (JNK), a stress-activated protein kinase, has been previously implicated in the process of cardiomyopathy and cardiac conduction system disease by downregulation of the gap junction protein connexin 43 [32,33], and cardiomyocyte apoptosis [34]. However, the present study showed no c-Jun activation in hearts from Lmna +/-mice.…”
Section: Discussioncontrasting
confidence: 76%
“…Activation of MAPK signaling cascade has recently been identified in hearts from mice homozygous for the LMNA mutation H222P [23], and this molecular pathway has previously been implicated in the development of cardiomyopathy, conduction defects [32,33] and apoptosis [34].…”
Section: Mitogen-activated Protein Kinase (Mapk) Signaling In the Dismentioning
confidence: 99%
“…80 However, in vivo JNK activation in transgenic animal models failed to induce cardiac hypertrophy. [81][82][83][84] Rather, the transgenic animals developed lethal restrictive cardiomyopathy with no myocyte hypertrophy but a significant induction of fetal gene expression. However, the direct impact (at the earliest time point) of JNK activation on cardiac gene expression and function remains unclear and should be studied by achieving inducible JNK activation in the adult heart as reported.…”
Section: Jnk Pathway In Cardiac Hypertrophymentioning
confidence: 99%